Understanding the mental well-being of older adults in care homes - CAITLIN REID (2022)
Older adults’ mental well-being is often overlooked, even though many stressors and triggers of mental health issues are experienced in later life. These may include the loss of family and friends through bereavement and the loss of ability and independence (Forbes-Thompson & Gessert, 2006). One of the main findings from the Older People’s Commissioner for Wales’ report ‘A Place to Call Home?’ (2014) was that there was a risk that older adults in care homes become institutionalised. Being in this kind of environment would have a significant impact on an individual’s mental well-being. To date there has been limited research into the experiences of older adults in care homes and what contributes to their mental well-being (Denning & Milne, 2011). The purpose of this PhD research was to better understand the mental well-being of older adults in care homes and look at ways to maintain and promote it. A mixed methods research design was developed to address these questions. The first quantitative stage used the Mental Health Continuum Short Form (MHC) to measure the mental well-being of 141 older adults from 23 care homes in South Wales. One of the findings from the first stage were that younger residents were more likely to have lower levels of mental well-being. The findings were then used to inform and develop the interview questions for the second qualitative stage of the research. The second stage comprised of twenty interviews with residents from six care homes. The interviews aimed to explore what was important to residents’ mental well-being. Reflexive thematic analysis (RTA) was used to analyse the interviews and generate themes important to residents’ mental well-being. Analysis indicated that residents experienced many losses in later life and since moving to a care home which impacted their mental well-being. The themes generated from the Reflexive Thematic Analysis (RTA) of residents’ experiences of what contributed to their mental well-being were ‘challenges to liberty’, ‘changes in identity’, and ‘importance of relatedness’. By considering these three themes, it is possible to better understand and offer recommendation on how to help maintain and promote the mental well-being of older adults in care homes.